FLYING INTO THE WORLD OF IMAGINATION: THE EFFECTIVENESS OF STORYTELLING IN CIRCLE TIME TO IMPROVE PROSOCIAL BEHAVIOR IN PRESCHOOL CHILDREN - Januarti, Andini; Ryanto, Syifa; Zahra. S, Viola Alya; Dita, Izmi Ayuning; Rahmi, Tuti (PT Altin Riset Publishing, 2025)
Prosocial behavior is a voluntary action that provides benefits to others, such as showing care, empathy, and respect for personal value and dignity. The ability to behave socially is very important to have in order to prepare oneself to be accepted in the social environment. The purpose of this study was to determine the effectiveness of storytelling in circle time on prosocial behavior in kindergarten children. The method used in this study is an experimental research method which uses one group pre-test post-test. Data collection was done through observation with checklist recording techniques. The data analysis used is descriptive analysis. The subjects in this study were TUNAS BANGSA kindergarten children aged 5-6 years. The results of this study are that the storytelling method at circle time is effective in increasing prosocial behavior in children.